A Linguistic Study of Metadiscourse Markers in Local Government Regulation for Tourism Development - Ekawati, Rosyida; Izzak, Arif; Puspitasari, Desi (Makassar State University, 2024)
Abstract. Study on metadiscourse covers various genres of texts, both academic and non-academic texts. This study concerns the genre of regulation that is still rarely studied. It aims to explain the types and functions of metadiscourse in local government regulation. By using descriptive qualitative design, it studied the local government regulation for Sumenep tourism development in particular for the front matter and the section of the core content of the regulation, excluding part of the explanation or attachment. Data in the form of clauses and sentences used which contain metadiscourse markers. Results of the study have shown that there are transitions, endophoric markers, and evidentials of interactive metadiscourse. There are no frame markers and code glosses. Endophoric markers are the most frequently used functions to refer to information from the text previously stated, evidentials that refer to information from other texts are mainly used to refer to other forms of the constitution, laws, ministerial regulation, and other government regulations as the basis of regulation drafting, and the least is transitions that functions to relate between main clause to be coherent and easily understood as a whole text. Meanwhile, all categories of interactional metadiscourse markers are not found in this genre of regulation. The use of metadiscourse markers can assist in engaging the reader by signaling the writer's attitude, position, or assessment of the presented information. This can render the text more interactive and persuasive.Keywords: metadiscourse, regulation, tourism, Sumenep, Madura